Analysis of HIV prevalence among pregnant women in Liangshan Prefecture, China, from 2009 to 2015. - Shujuan Yang; Chao Yang; Qiang Liao; Wenwen Zhai; Gang Yu; Lin Xiao; Qixing Wang; Yuhan Gong; Suhua Zhang; Yongna Yao; Ke Wang; Ju Wang; et al. (PLoS ONE)
Background Yi people make up about 50% of the population in Liangshan Prefecture, Sichuan Province, China, but accounted for 88.07% of new HIV cases in the prefecture from 2011 to 2013. This study evaluated HIV prevalence in pregnant women of Liangshan Prefecture using HIV sentinel surveillance (HSS) data over the period of 2009 to 2015. Methods Xichang, Zhaojue County, and Butuo County were selected as HSS sites. We investigated the temporal trends in HIV prevalence in these areas, and the association between demographic and behavioral characteristics and risk of HIV infection. Results Data on a total of 2797 pregnant women in Xichang and 3983 pregnant women in Zhaojue and Butuo was collected for the period 2009 to 2015. There was a fluctuating HIV prevalence among pregnant women of Xichang, with a rate of 0.75% in 2015 (χ2trend = 2.27, P = 0.13). HIV prevalence among pregnant women of Zhaojue and Butuo was consistently high, varying between 3.4% (9/267, 2011) and 10.3% (82/796, 2012) over the period of 2010 to 2015 (χ2trend = 0.12, P = 0.73). In Xichang, we found that Yi ethnicity (OR = 11.37, 95% CI = 2.92-44.25) and a husband who used drugs (OR = 32.13, 95% CI = 5.33-193.67) were significantly associated with HIV risk in pregnant women. For Zhaojue and Butuo, we observed that pregnant women had a higher risk of HIV infection when they were over 30 years old (OR = 1.72, 95% CI = 1.17-2.52), when they had a higher number of previous births, when their husbands had a history of migrating for work (OR = 1.56, 95% CI = 1.16-2.08), and when they had a history of other sexually transmitted infections (OR = 2.19, 95% CI = 1.16-2.08). Compared to those with a primary school education or below, pregnant women with a secondary or high school education level had a lower risk of HIV infection (OR = 0.28, 95% CI = 0.09-0.89). Conclusion Our results indicate that there is a serious HIV epidemic among pregnant Yi women, especially for those with less education, more past births, or a husband with a history of out-migrating for work or STD infection.